Performance analysis of coordinate interleaved plc system with rayleigh channel gain under nakagami-m additive noise - Sikri A.; Mathur A.; Srinivas K.V. (My University, 2025)
Power line communication (PLC) is an emerging field of communication that makes use of the existing power line infrastructure for the transmission of data and power. However, the presence of additive and multiplicative power line noises deteriorate the performance of a PLC system. Background and impulsive noises are the two main categories of additive noise, whereas channel gain accounts for the multiplicative noise. In this study, the authors propose coordinate interleaving (CI) technique and investigate its performance for a PLC system under the combined effect of Nakagami-m additive background noise and Rayleigh channel gain. They assume perfect channel state information at the transmitter and receiver of the PLC link. By interleaving the coordinates of the symbols sent over different channel realisations, CI results in significant improvement in the performance of a PLC system. Both the simulated and analytical results shown in this study reveal the effectiveness of the proposed technique in achieving better performance. © The Institution of Engineering and Technology 2019.